Merry Christmas, Cheeps! - Stiegemeyer, Julie (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
A family of chicks celebrates the joys of the Christmas season, from making snow angels and baking cookies to hanging ornaments on the tree and joyfully bouncing down the stairs on Christmas morning.